Políticas Laborales en España para los Inmigrantes - Sacristán Romero, Francisco (Acta Universitaria, 2006)
The active work policies for the immigrant group try to contribute to the increase of the incorporation possibilities and labor maintenance of these workers so related to the Spanish culture, combining, at the same time, flexibility and security in the use. In addition, in macroeconomic terms, the selective performance on the supply and the demand, with measures such as the promotion of the private initiative, the aid to mobility to sectors with sufficient demand or the direct creation of employment, allow the reduction of the imbalances or misalignments in the work market.